A Novel Method for Treating Bronchial Asthma with Newly Designed Histaglobulin Therapy - Sivanandhan K; Dhanalakshmi S (International Journal of Pharma and Bio Sciences, 2022)
Asthma, a chronic inflammatory disease of the airways is considered as an incurable disease and extensive research is going on in developing novel treatment. The objective of the study is to establish that the antihistamine antibody has low serum histamine binding capacity (SHBC) in allergic patients as compared to normal persons and that it can be raised with our novel method of Histaglobulin treatment thereby effecting a ‘cure’ in bronchial asthma. About 67 normal and 135 allergic persons, were identified based on serum level of total immunoglobulin E (IgE) estimated by ELISA. Antihistamine antibody was separated from serum by affinity chromatography. Presence of antihistamine antibody in the elute was confirmed by SDS-PAGE test. The antihistamine antibody was IgG, confirmed by MALDI-TOF analysis. The SHBC of the antihistamine antibody was estimated based on standard curve, plotted with different concentrations of serum antihistamine antibody by histamine ELISA test. Total Immunoglobulin E and SHBC were estimated in 135 allergic patients. In normal and allergic persons, the total IgE level was <100 IU/ml and 200 IU/ml respectively. The average SHBC of normal persons was 116 µg/ml, which was 39% more as compared to allergic patients whose average SHBC before treatment was 83.6 µg/ml. 135 allergic patients were first subjected to antihistamine, mast cell-membrane stabilizers, anti-inflammatory and bronchodilator drugs followed by histaglobulin injection. The SHBC level was raised in 122 (90.4%) patients to an average of 111.6 µg/ml. Overall, 132 (97.8%) allergic patients responded well to our treatment and were free from allergic manifestation throughout the follow-up period of about 5 years. Hence, this novel treatment with histaglobulin which has scientific basis, effective and well tolerated can be adopted across the world for effecting a cure from bronchial asthma and allergic rhinitis.